2009
DOI: 10.1603/022.038.0306
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Imported Fire Ants (Hymenoptera: Formicidae) on a Sheep and Goat Farm in Oklahoma

Abstract: Imported fire ant colonies were quantified in 1,000-m(2) circular subplots spaced approximately 125 m apart on a sheep and goat farm in Oklahoma. Social form (percent polygyny), mound density, cumulative above-ground mound volume, and average mound volume were subjected to multiple regression analyses to examine trends related to landscape metrics and habitat characteristics. Monogyne populations were spatially autocorrelated, and polygyne mounds tended to be smaller and more numerous. A model incorporating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The results of this study indicate that disturbance from low-intensity prescribed burning did not affect RIFA abundance around ponds in our study area. This finding is in contrast to other studies reporting that disturbance from livestock use or vegetation clearing can lead to increases in RIFA abundance (Lofgren et al 1975;Stiles and Jones 1998;Todd et al 2008;Vogt et al 2009). In the present study, the number of RIFAs captured at the two summer burn ponds decreased immediately after burning, but it returned to background levels within weeks.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study indicate that disturbance from low-intensity prescribed burning did not affect RIFA abundance around ponds in our study area. This finding is in contrast to other studies reporting that disturbance from livestock use or vegetation clearing can lead to increases in RIFA abundance (Lofgren et al 1975;Stiles and Jones 1998;Todd et al 2008;Vogt et al 2009). In the present study, the number of RIFAs captured at the two summer burn ponds decreased immediately after burning, but it returned to background levels within weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…In primarily forested habitats, RIFA tends to be more abundant in forest gaps (Colby and Prowell 2006). Red imported fire ants are adapted to periodically flooded habitats (Allen et al 1974) and have been found to prefer edges of ponds and other water bodies (Lyle and Fortune 1948;Tschinkel 1988;Stuble et al 2009;Vogt et al 2009). Because RIFA can be more flood tolerant than some native ant species, it may have a competitive advantage over these taxa in flood-prone environments (Vogt et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Brisbane, differences of up to 20-30 °C (average +11.9 °C, n = 1467) have been recorded, making them highly visible with thermal imagery, whereas recorded temperature differences were only up to 10 °C between mounds and their surroundings in Mississippi studies (Vogt et al 2008a). As reported from remote sensing trials in the United States, a range of factors can affect the capture of suitable imagery, including nest location (obscured or in the open), mound shape, weather conditions, time of year and soil type (Vogt 2004a, b;Vogt et al 2008a, b;Vogt et al 2009). Similar findings were made in southeast Queensland and incorporated into operational guidelines.…”
Section: Image Capturementioning
confidence: 99%
“…Higher densities of mounds are reported for North American harvester ants ( Pogonomyrmex spp. : 20–150 nests ha –1 ; MacMahon et al ., 2000) and fire ants ( Solenopsis invicta : 50–220 nests ha –1 ; Vogt et al ., 2009). Exceptionally, the densities of anthills created by Lasius flavus can reach up to 2500 mounds ha –1 in some parts of the Baltic region and the British islands (Elmes, 1991).…”
Section: Direct Geomorphic Effects Of Insectsmentioning
confidence: 99%